Penguatan dan Pendampingan Karya Tulis Ilmiah Guru MIN 8 Nganjuk - Moh. Irmawan Jauhari; Muhammad Yunus; Siti Albadriyah; Nor Cholis (Lembaga Pengembangan Kinerja Dosen, 2025)
The focus and objective of the community service program is to empower teachers at MIN 8 Nganjuk and its surrounding areas to maximize their scientific writing. While scientific writing in the form of PTK is an administrative obligation, it also provides a positive contribution to improving learning. The Asset-Based Community-Driven Development (ABCD) method prioritizes the utilization of existing assets and potential. The ABCD steps include Discovery (discovering potential), Dream (shared dreams), Design (program design), Define (determining concrete steps), and Destiny (determining goals and implementation). The results of the mentoring program indicate that the teachers have a good foundation in writing scientific papers. However, they are still hampered by busy administrative routines. The training aims to stimulate writing enthusiasm and bridge the realization of book chapters among teachers. This mentoring is expected to have a positive impact on improving the quality of teachers' scientific work and improving the learning process at school. In addition, this program also aims to build a sustainable writing culture among educators.